How accurate and useful are published UK prevalence rates of intimate partner violence (IPV)? Rapid review and methodological commentary. Issue 2 (12th July 2021) - Ali, Parveen; Allmark, Peter; Booth, Andrew; Seedat, Farah; Woods, Helen B; McGarry, Julie
Abstract : Purpose: This paper aims to estimate the prevalence of intimate partner violence (IPV) in the UK general population and in the low-risk clinical population and to identify the methodological challenges presented by this task. Design/methodology/approach: A rapid review of the evidence was conducted. Data were extracted with the help of pre-designed tools and were synthesised to answer the two study aims. The data extracted was both qualitative and quantitative. Findings: In the general population, crime survey data gave a range of past-year IPV prevalence from 1.8% to 4.5%. This was higher in women than men (2.5%–6.3% vs 0.9%–2.7%). In both the general and low-risk clinical population, there was little data on pregnant women or gay men and lesbians. No significant relationships between IPV and ethnicity were found. Different surveys used different definitions of IPV and domestic violence, making it difficult to give an accurate estimate. There were also problems with data accuracy. Originality/value: This research is original and contributes to the knowledge about IPV screening and if prevalence studies help.